Policy for Addressing Beggars in the Pilgrimage Tourism Area of Sunan Gunung Jati Tomb - Tiara Ivana; Shafira Amalia Putri; Yanto Heryanto (PT Publikasiku Academic Solution, 2025)
This research analyzes the tourism policy regarding beggars in the pilgrimage area of the Sunan Gunung Jati Tomb, where begging has become a tradition rooted in Sunan Gunung Jati’s will: